2015
DOI: 10.1002/mrm.25723
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural parameter estimation in vivo using diffusion MRI and structured prior information

Abstract: PurposeDiffusion MRI has recently been used with detailed models to probe tissue microstructure. Much of this work has been performed ex vivo with powerful scanner hardware, to gain sensitivity to parameters such as axon radius. By contrast, performing microstructure imaging on clinical scanners is extremely challenging.MethodsWe use an optimized dual spin‐echo diffusion protocol, and a Bayesian fitting approach, to obtain reproducible contrast (histogram overlap of up to 92%) in estimated maps of axon radius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Thus, their relationship needs to be appropriately modelled and care must be taken when comparing dMRI measures with the V V distributions. Finally, the characterisation of the V V distributions in the population could inform dMRI biophysical models as prior distributions to improve the accuracy of the estimated parameters (Clayden et al, 2016).…”
Section: Global Results (N¼30)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, their relationship needs to be appropriately modelled and care must be taken when comparing dMRI measures with the V V distributions. Finally, the characterisation of the V V distributions in the population could inform dMRI biophysical models as prior distributions to improve the accuracy of the estimated parameters (Clayden et al, 2016).…”
Section: Global Results (N¼30)mentioning
confidence: 99%
“…This information has the potential to improve the performance of existing tissue models and help in the validation of new ones. For example, Clayden et al (2016) showed that by introducing structured prior information on model parameters, the accuracy in the estimation is improved. The interpretation of parameters from several existing dMRI techniques such as DTI or biophysical models has been previously validated using histological sections (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian modeling has found application as a tool for image processing and parameter estimation across a broad range of MRI domains (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Neil and Bretthorst (28) were the first to propose its use as an alternative to nonlinear least squares fitting for improving the quality of IVIM parameter estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al, 2012), use of structural models to infer tissue micro-structure (e.g. Lekadir et al, 2014Lekadir et al, , 2015Clayden et al, 2016), use of computational models to produce virtual images of unobservable features (e.g. Nørgaard et al, 2016;Lekadir et al, 2016), or computational imaging approaches that incorporate prior knowledge into image acquisition or reconstruction leading, for instance, to agile or portable imaging/sensing systems (York et al, 2011;Coskun and Ozcan, 2014).…”
Section: The Trend: From Data To Wisdom and Backmentioning
confidence: 99%